Fiscal dynamics in Ethiopia: The cointegrated VAR model with quarterly data - Pedro M. G. Martins (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2010)
This paper uses the cointegrated vector autoregressive (CVAR) model to assess the dynamic relationship between foreign aid inflows, public expenditure, revenue and domestic borrowing in Ethiopia. It departs from the existing literature by using a unique quarterly fiscal dataset (1993-2008) and providing new insights into the formulation of testable fiscal hypotheses. The paper also derives and interprets structural shocks and places a strong focus on model specification. The results suggest the presence of three long-run relationships: the government budget constraint, a donor disbursement rule, and a financing trade-off. Foreign aid grants adjust to the level of development spending, which can be seen as an indication of (procyclical) aid conditionality. Moreover, domestic borrowing often compensates for lower levels of revenue and grants, highlighting the cost of aid unpredictability and revenue volatility. The policy implication is that if foreign aid flows are to be made more effective, they should be provided in a predictable and countercyclical fashion in order to smooth exogenous shocks.
Keywords: C32; F35; O23; O55; 330; Fiscal Response; Foreign Aid; Time Series Models; Africa; Entwicklungshilfe; Kapitalimport; Öffentliche Einnahmen; Öffentliche Ausgaben; Öffentliche Schulden; Konjunktur; VAR-Modell; Äthiopien